Getting growth accounting right (2015)
Variation in factor shares, extensively documented in recent years, implies that standard growth accounting exercises are plagued by measurement issues. First, the standard assumption of constant shares generates a bias in the estimation of the contribution of factors to economic growth. Second, the effect that changes in factor shares have on output depends on the relative abundance of factors and, for this reason, having correct units of measurement for all factors is imperative. We perform a growth accounting exercise that incorporates factor share variation and solves the measurement issue. Results suggest that (i) the correct units of measurement are significantly lower than standard ones for the stocks of physical, natural and human capital per worker (ii) changes in factor shares have an important effect on the growth rates of income per worker for several countries and (iii) the marginal productivity of all factors is positively correlated with per worker income.